Comparison of Awareness and Computer Literacy in Classes through Creation of Storytelling and Product Introduction Slides - Miyaji, Isao (American Journal of Education and Learning, 2019)
In order to ensure that university students have a sound base of computer knowledge and operating ability, and in order to improve their awareness related to their abilities, two types of classes were offered in which storytelling and product slide presentations were performed by creating slides using PowerPoint, entering awareness and evaluations by others using Excel, and creating and submitting reports using Word. This paper investigates differences in the outcomes resulting from differences in the themes, and explores potential reasons for these differences. It compares and examines the amount of time taken to complete the works and the awareness of the students with regard to these abilities. Their abilities to use software functions are surveyed and differences between two classes are compared and revealed. After comparing usage abilities of individual software functions, the results of variance analysis of the average usage ability for each of the three types of software for two classes are shown.